A Mayan founder mutation is a common cause of deafness in Guatemala. Issue 4 (6th October 2015) - Carranza, C.; Menendez, I.; Herrera, M.; Castellanos, P.; Amado, C.; Maldonado, F.; Rosales, L.; Escobar, N.; Guerra, M.; Alvarez, D.; Foster, J.; Guo, S.; et al.
Abstract : Over 5% of the world's population has varying degrees of hearing loss. Mutations in GJB2 are the most common cause of autosomal recessive non‐syndromic hearing loss (ARNHL) in many populations. The frequency and type of mutations are influenced by ethnicity. Guatemala is a multi‐ethnic country with four major populations: Maya, Ladino, Xinca, and Garifuna. To determine the mutation profile of GJB2 in a ARNHL population from Guatemala, we sequenced both exons of GJB2 in 133 unrelated families. A total of six pathogenic variants were detected. The most frequent pathogenic variant is c.131G>A (p.Trp44*) detected in 21 of 266 alleles. We show that c.131G>A is associated with a conserved haplotype in Guatemala suggesting a single founder. The majority of Mayan population lives in the west region of the country from where all c.131G>A carriers originated. Further analysis of genome‐wide variation of individuals carrying the c.131G>A mutation compared with those of Native American, European, and African populations shows a close match with the Mayan population.